KEPENTINGAN AMERIKA SERIKAT MENANDATANGANI MEMORANDUM OF UNDERSTANDING (MOU) TENTANG PEMBERIAN BANTUAN KEAMANAN TERHADAP ISRAEL TAHUN 2016 - Yanto, Fajri Juni; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
On 14 September 2016 the US and Israeli governments through their representatives signed a new MOU on the provision of security assistance to Israel. This MOU is the largest security funding deal in the history of the United States. Not less than $ 38 billion will be awarded to the Israel by United States in the form of Foreign Millitary Funding (FMF) as much $33 billion and a missile defense cooperation fund as much $5 billion. The research will explain what caused the United States to approve the signing of the MOU.This research theoretically has built with Kenneth Waltz Neorealism perspective and theory, as the only flow of thought in this research. Formulation of all arguments, data, facts, and theoritical framework in this research is adopting the qualitative explanation methodology. It takes international system as the level of analyzing, the focus on this research is explaining the causes of United States signed MOU on providing security assistance against israel.Reseacrher has formulated answer-hypothesis which revealed the fact that The development of security threats on israel in the middle east area has caused United States signed MOU on providing security assistance against Israel. As strategic asset of the United States in the Middle East region, with rising security threats coming from Hezbollah, Hamas and rising political threats from Iran and Syrian, US has to protect its staregic asset by providing security assistance to improve Israel's Qualitative Military Edge (QME) to defend itself by it self.Keywords: United States, Israel, MOU, Security Assistance, FMF, QME, Strategic Asset